PENGARUH PEMBELAJARAN MENULIS TERHADAP KEMAMPUAN MENULIS TEKS ULASAN PADA SISWA KELAS VIII DI MTS USHULUDDIN SUNGAI JAGA A KABUPATEN BENGKAYANG - Anisa, Rahmatul; Seli, Sesilia; Muzammil, Ahmad Rabiul (Universitas Tanjungpura, 2025)
This research aims to determine the effect of learning to write on the ability to write review texts in class VIII students at MTs Ushuluddin Sungai Jaga A, Bengkayang Regency. The research method used is descriptive to describe the influence of learning to write on students' ability to write review texts, using the form of quantitative research. The research sample was 40 class VIII students at MTs Ushuluddin Sungai Jaga A, Bengkayang Regency, academic year 2023/2024. The data collection technique is a test technique in the form of essay questions. The data analysis technique used in this research is descriptive statistics. The results of this study show that there is an influence of learning to write on the ability to write review texts in class VIII students at MTs Ushuluddin Sungai Jaga A. There is an influence of learning to write simultaneously on the ability to write the structure of review texts by 0.000 below the predetermined significance level value of 0.05 , there is an influence of learning to write simultaneously on the use of aspects of linguistic rules of the review text of 0.000 below the predetermined significance level value, namely 0.05, there is an influence of learning to write simultaneously on the accuracy aspect of the content of the review text of 0.000 below the significance level value that has been determined determined to be 0.05, and the ability to write review texts for class VIII students at MTs Ushuluddin Sungai Jaga A, Bengkayang Regency. The average score in the structural aspect is 85,5, the average score in the linguistic rules aspect is 64,7, the average score in the content accuracy aspect is 73,3 and the average score in the ability to write review texts for class VIII students MTs Ushuluddin Sungai Jaga A Bengkayang Regency from these three aspects is 75 in the capable category.